MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS MEDIA FLASCH CARD UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK KELAS IA SDN KALIRUNGKUT I/264 SURABAYA - Mega Rista Saras Ati; Lina Listiana; Diah Eka Sulistyorini (PROCEEDING UMSURABAYA, 2024)
This study was conducted to determine the motivation and learning outcomes of reading by using the discovery learning model for class IA students of SDN Kalirungkut I/264 Surabaya. The research method used quasi experiment. The subjects of this study were 22 students. The research instrument used was a test sheet totaling 10 questions, learning implementation sheet, student reflection, attitude observation sheet, and skill observation sheet. Data collection techniques were carried out using observation, test, and questionnaire methods. The research data were analyzed through the results of the implementation of the discovery learning model, skill sheets, student response questionnaire data. The results of the implementation of learning averaged 98 with a very good category, the results of mutual cooperation attitudes 81. 8 with a developing category, the results of pre-test knowledge 83. 6 and post-test 95. 45, and the results of critical reasoning skills through observation of 96. 5 with a very good category and the results of communication skills 98. 8 with a very good category. The use of flash card learning media is very effective related to student reading for short-term memory and if continued will enter into long-term memory. The conclusion of the discovery learning model can improve students' skills towards mutual cooperation, critical thinking, motivation and student learning outcomes to increase.